Effectiveness of dabrafenib in the treatment of patients with BRAF V600–mutated metastatic melanoma in a Named Patient Program. Issue 5 (October 2019) - Martin-Algarra, Salvador; Hinshelwood, Rebecca; Mesnage, Soizick; Cebon, Jonathan; Ferrucci, Pier Francesco; Aglietta, Massimo; Neyns, Bart; Chiarion-Sileni, Vanna; Lindsay, Colin R.; Del Vecchio, Michele; Linardou, Helen; Merelli, Barbara; et al.
Abstract : Given the approval of dabrafenib in patients with BRAF -mutant metastatic melanoma, a better understanding of treatment patterns and clinical outcomes with dabrafenib in a clinical setting is warranted. We performed a retrospective chart review of patients who received dabrafenib in a compassionate use setting through the Named Patient Program (DESCRIBE I study) during December 2010–August 2013 in Europe, New Zealand and Australia. Of the 331 Named Patient Program patients included, the majority (95.8%) had stage IV disease at dabrafenib initiation and 39.9% had brain metastases (BMs). Dabrafenib was used first line in 67.7% of patients, and median treatment duration was 6.4 months. Dabrafenib was well tolerated. Common grade 2/3 adverse events were hyperkeratosis (7.6%), pyrexia/fever (6.6%), fatigue (5.1%), hand-foot syndrome (5.4%) and nausea (3.6%). Overall response rate was 45.9%, median progression-free survival was 5.2 months (95% confidence interval, 4.2–6.1 months), and median overall survival was 12.4 months (95% confidence interval, 10.2–15.0 months). In patients with known brain metastases ( n = 132) versus patients without ( n = 199), overall response rate was 42.4% versus 48.2%, progression-free survival was 3.9 months (95% confidence interval, 3.8–5.5 months) versus 5.9 months (95% confidence interval, 4.8–7.8 months) and overall survival was 9.5 months (95% confidence interval, 6.7–12.4 months) versus 15 months (95% confidence interval, 11.1–20.5 months), respectively. Safety and effectiveness of dabrafenib in patients with unresectable advanced BRAF V600–mutant melanoma treated in an Named Patient Program was similar to the clinical trial experience, demonstrating effectiveness of dabrafenib in a nontrial setting. Abstract : Supplemental Digital Content is available in the text.